Penerapan Kompetensi Guru Anak Usia Dini Dalam Menstimulasi Keterampilan Berbicara Pada TK Negeri Pembina Giri Mulya - Dwi Rahayu Ningsih, Endang; Ismilia, Mike; Hidayat, Tomi; Asmara, Adi (STIA Bengkulu, 2025)
Early childhood education holds an essential function in promoting the comprehensive growth of young children through well-planned and organized learning activities. This research focuses on analyzing how early childhood educators at Pembina Giri Mulya State Kindergarten apply their professional competencies to encourage the development of children's speaking abilities. Employing a descriptive qualitative approach, the research explores real conditions in the educational setting. The Data collected using observation, interviews, and documentation techniques. The results indicate the teachers effectively apply various learning methods—such as storytelling, conversation, and singing—to enhance children's verbal communication abilities. These approaches play an essential role in enhancing children's self-confidence, verbal expression, and ability to interact socially.